Relationship between facial morphology, anterior open bite and non-nutritive sucking habits during the primary dentition stage - Fialho,Melissa Proença Nogueira (2014)
INTRODUCTION: Non-nutritive sucking habits (NNSHs) can cause occlusal alterations, including anterior open bite (AOB). However, not all patients develop this malocclusion. Therefore, the emergence of AOB does not depend on deleterious habits, only. OBJECTIVE: Investigate a potential association between non-nutritive sucking habits (NNSHs), anterior open bite (AOB) and facial morphology (FM). METHODS: 176 children in the primary dentition stage were selected. Intra and extraoral clinical examinations were performed and the children's legal guardians were asked to respond to a questionnaire comprising issues related to non-nutritive sucking habits (NNSHs). RESULTS: A statistically significant relationship was found between non-nutritive sucking habits (NNSHs) and anterior open bite (AOB). However, no association was found between these factors and children's facial morphology (FM). CONCLUSIONS: Non-nutritive sucking habits (NNSHs) during the primary dentition stage play a key role in determining anterior open bite (AOB) malocclusion regardless of patient's morphological facial pattern (FM).